Private military and security companies: the end of state responsibility? (2019)
The objective of this article is to observe the redefinition of state responsibility based on its interaction with Private Military Security Companies. The boom, consolidation and decline of these companies between the end of the Cold War era and the first decade of the 21st century pose a dilemma to international law regarding State responsibility towards security issues within its territory. The lack of effective international law mechanisms and the political agenda of the States are both limitations for preserving human dignity in institutional and humanitarian fragile contexts. Hence, an interdisciplinary approach must be considered in order to seek an alternative path to this dilemma. This research used empirical data and documental analysis to achieve this objective.